Acknowledgement of Excellent for 17 of UMP Advanced Staff - Nor Salwana, Mohammad Idris (2020)
Kuantan, 25 September 2029 – UMP Advanced appreciates the excellent performance shown by its member in the “Majlis Sekalung Budi UMP Advanced” event that was held at Zenith Hotel, recently.